Anthropometric and Anthroposcopic Analysis of Periorbital Features in Malaysian Population: An Inter-racial Study - Packiriswamy, Vasanthakumar; Kumar, Pramod; Bashour, Mounir (Facial Plastic Surgery, 2018)
In oculoplastic operations, knowledge of the dimensions of periorbital features based on age, gender, and race is essential for achieving better aesthetic result. This article seeks to determine the racial and gender differences of periorbital features among Malaysian Malay (MM), Malaysian Indian (MI), and Malaysian Chinese (MI) subjects. Evaluation of periorbital features was done on photographs of 200 MM, 200 MI, and 200 MC subjects, aged 18 to 26 years. The measured values were evaluated by an independent t-test. A significant difference was found between MM and MI in all measurements except interbrow distance in males, eyebrow thickness in females, and apex to lateral limbus distance in both sexes. Between MI and MC the difference was insignificant for interbrow distance in male groups, apex to lateral limbus distance in females, and palpebral fissure inclination and eyebrow apex angle in both sexes. Between MM and MC, significant differences were found for eyebrow thickness and medial canthus tilt in female group. Male groups showed significant difference for apex to lateral limbus and lateral canthus distance and eyebrow apex angle. Eyebrow height, palpebral fissure width, and intercanthal distance were significantly different in both sexes. Sexual dimorphism was found for all measurements in MI, but MM and MC showed insignificant difference for eyebrow apex angle. Four types of epicanthus were observed in MM and MC and three types in MI. Eyebrow apex between lateral limbus and lateral canthus was the most common position in all racial groups. Significant racial and gender differences exist for certain periorbital measurements. The knowledge of these differences is expected to influence the surgical outcome.
Keywords: periorbital features; aesthetic anatomy; sexual dimorphism